Efficacy and Safety of Perioral Mound Region Liposuction–A Novel Concept to Improve Perioral Mound Fullness. (3rd January 2023) - Gu, Yunpeng; Yang, Mingzi; Li, Jiyang; Sun, Jingjing; Lv, Qianwen; Qi, Yue; Han, Xuefeng; Qi, Zuoliang; Ma, Gui-e
Abstract: Background: Fullness of the perioral mound is considered a dissatisfying aspect of premature aging and has become a common complaint of patients seeking facial rejuvenation. Objectives: The authors propose a novel concept of improving perioral mound fullness by liposuction and verify its safety and efficacy through cadaver and clinical studies. Methods: A cadaver study was conducted to discover the soft tissue structure of the perioral mound region and identify a vital use for liposuction. For clinical evaluation, 37 patients with perioral mound fullness who underwent liposuction were retrospectively reviewed. Results: The cadaver study results showed moderate fatty tissue in the subcutaneous layer of the perioral mound region. The liposuction manipulation was limited to the subcutaneous fat layer. Among the 37 patients (including 74 perioral mound regions), the median fat removal volume per perioral mound region was 2.0 (1.2, 2.3) mL. After liposuction, the subcutaneous fat thickness significantly decreased (median 5.0 [3.9, 6.6] mm vs 0.7 [0.4, 1.0] mm per perioral mound region, P < .001). All patients were satisfied with their posttreatment outcomes. Two patients (5.4%) had slight skin hyperpigmentation in the liposuction area after treatment and recovered naturally in 3 months without any intervention. No other complications were noted. Conclusions: Liposuction is effective in improving perioral mound fullness with a low risk of complications. Level of Evidence: 4: